Evaluation of the Pharmacokinetics of Intranasal Drug Delivery for Targeting Cervical Lymph Nodes in Rats - Tomoyuki Furubayashi; Daisuke Inoue; Shunsuke Kimura; Akiko Tanaka; Toshiyasu Sakane (MDPI AG, 2021)
A well-developed lymphatic network is located under the nasal mucosa, and a few drugs that permeate the nasal mucosa are absorbed into the lymphatic capillaries. Lymph from the nasal cavity flows to the cervical lymph nodes (CLNs). In this study, we evaluated the pharmacokinetics of the direct transport of intranasally administered drugs to CLNs through the nasal mucosa of Wistar rats using methotrexate as a model drug. The drug targeting index, which was calculated based on the areas under the concentration-time curves after intravenous and intranasal administration, was 3.78, indicating the benefits of nasal delivery of methotrexate to target CLNs. The direct transport percentage, which was indicative of the contribution of the direct nose-CLN pathway of methotrexate after intranasal administration, was 74.3%. The rate constant of methotrexate from the nasal cavity to CLNs was 0.0047 ± 0.0013 min−1, while that from systemic circulation to CLNs was 0.0021 ± 0.0009 min−1. Through pharmacokinetic analysis, this study demonstrated that the direct nasal-CLN pathway contributed more to the transport of methotrexate to the CLNs than the direct blood-CLN pathway.